Respuesta :
Hey there!
The solution to the system is [tex](\frac{1}{2}, 13)[/tex]
To solve the system, we can multiply the second equation by -1:
[tex]-2x - y = -12[/tex]
Then, we add the two equations together, and solve for x:
[tex]4x = -2[/tex]
[tex]x = \frac{-1}{2}[/tex]
Now, we plug the x value into one of the equations, and solve for y:
[tex]2(\frac{1}{2} ) + y = 12[/tex]
[tex]-2 + y = 12[/tex]
[tex]y = 13[/tex]
Now we know that the solution to the system is [tex](\frac{1}{2}, 13)[/tex]
Hope it helps and have an amazing day!
Answer:
(-1/2, 13)
Step-by-step explanation:
Multiply the 2nd equation by -1, obtaining the following system:
6x + y = 10
-2x - y = -12
------------------
Combine like terms, obtaining:
6x + y = 10
-2x - y = -12
------------------
4x = -2
Dividing both sides by 4 yields x = -2/4, or x = -1/2
Substituting -1/2 for x in the second equation yields:
2(-1/2) + y = 12, or
-1 + y = 12. Then y = 13, and the solution is
(-1/2, 13)